The Accuracies of Fine-Needle Aspiration Biopsy without Ultrasound Guidance versus Frozen-Section Examination of Thyroid Nodule Diagnosis in Teaching Hospital Universitas Sumatera Utara: Single-Center Experience - Hermansyah, Dedy; Siregar, Denny Rifsal; Siregar, Erwin Sahat Hamonangan; Nasution, Iqbal Pahlevi Adeputra; Harahap, Arjumardi Azrah Khairul; Firsty, Naufal Nandita; Siregar, Kamal Basri (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The urgency to determine the most applicable methodological approach in thyroid nodules diagnosis workup is unquestionably important due to a significant increase in its prevalence globally. To date, fine-needle aspiration biopsy (FNAB) is the most recommended procedure to diagnose preoperatively even though the certain role of frozen-section examination (FSE) intraoperatively were significant as well to be administered at some circumstances. AIM: This study aims to measure the diagnostic accuracies of FNAB and FSE and determine the role of each procedure in the current thyroid nodules’ workup. MATERIALS AND METHODS: This retrospective study was conducted at teaching hospital of Universitas Sumatera Utara, Indonesia. We included and investigated both FNAB and FSE in 106 patients; the results were compared to the final histopathological report, in which statistical analyses were conducted. RESULTS: Most of the nodules are malignant after histopathological confirmation. From the fourfold contingency table, we were able to subtract several diagnostic parameters of the procedures. The FSE substantially disclosed better performance in sensitivity, specificity, positive predictive value (PPV), negative predictive value, and remarkably the accuracy. After several in-depth analyses, it is apparent that a higher rate of false-negative in FNAB is inducing its substandard performance, especially when the guidance of ultrasonography was not applied in this study. Furthermore, an analysis toward the concordance between both procedures results is revealing a significant improvement on almost every parameter, indicated by 100.0% specificity and PPV. CONCLUSION: Although the outcomes in this study are not corresponding to the current guidelines, we acknowledged several limitations in this study, However, the role of FSE in thyroid nodule workup should be reconsidered since we found that the procedure is exhibiting a potential to assist the current method, even though the influence of its certain pitfall remained questionable.